Wild vs. cultivated strawberries: differential fruit quality traits and antioxidant properties in Fragaria chiloensis and Fragaria × ananassa - Chamorro, Melina Fernanda; Mazzoni, Ariel Omar; Lescano, Maria Natalia; Fernandez, Anahí; Reiner, Gabriela; Langenheim, Mariana Elsa; Mattera, Maria Gabriela; Robredo, Nicolás; Garibaldi, Lucas; Quintero, Carolina (Springer, 2025)
Nature can contribute to human well-being in various ways, yet some culturally significant wild species remain understudied. This is the case with the red form of Fragaria chiloensis subsp. chiloensis, a wild relative of the cultivated strawberry, used in Argentine Patagonia for food, medicine, and functional foods. This study compares the fruit quality and biochemical traits of three wild ecotypes (F. chiloensis subsp. chiloensis) with cultivated strawberries (F. × ananassa), under common field conditions, to identify agronomic and health interest traits. Results support the domestication syndrome hypothesis, showing that cultivated strawberries exhibit better quality fruit attributes (larger size, greater firmness, and higher pigment content) but lower levels of the most beneficial compounds than wild strawberries. In particular, wild strawberries display higher total soluble solids, and higher content of total phenolics, ellagic acid, and cyanidin-3-glucoside, with significant variation among ecotypes. Moreover, wild strawberries showed superior antioxidant activity, especially through the DPPH assay, primarily driven by total phenolic and flavonoid content. This study highlights the potential of Patagonian strawberries for developing new, healthier fruits and underscores the importance of investigating wild relatives of crops to gain insights into the domestication process and identify beneficial traits.